2015
DOI: 10.1002/jssc.201500213
|View full text |Cite
|
Sign up to set email alerts
|

Determination of organophosphate esters in water samples by mixed‐mode liquid chromatography and tandem mass spectrometry

Abstract: A simple and sensitive method for the determination of organophosphate esters in water samples by mixed-mode liquid chromatography with electrospray ionization tandem mass spectrometry coupled with solid-phase extraction is developed. Using seven alkyl phosphates, three chlorinated alkyl phosphates, and four aryl phosphates as the targets, the developed method was systematically evaluated on the basis of the influence of the solid-phase extraction cartridge, eluting solvent, sample-loading volume, mobile phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 46 publications
2
10
1
Order By: Relevance
“…Of all the target compounds in this study, the predominance of TBEP, TCPP and TCEP were also observed in STP wastewater in most developed countries including Spain (Rodriguez et al, 2006;Quintana and Reemtsma, 2006;Garcia-Lopez et al, 2010), Germany (Rodil et al, 2005;Meyer and Bester, 2004), Austria (MartinezCarballo et al, 2007) and Sweden (Marklund et al, 2005) (Table 2). In the present study, raw sewage aqueous phase concentrations of TBEP, TCPP and TCEP were lower than those in surface water in Beijing: 10-740 ng/L TBEP, 145-1359 ng/L TCPP, and 88.4-2918 ng/L TCEP (Gao et al, 2015), which may result from the separation of rain and sewage considering that rainwash can directly bring a plenty of OPEs from soil, dust and airborne particles into the river. Meanwhile, the raw sewage aqueous phase concentrations of these three OPEs were lower than those in most developed countries (Table 2), e.g.…”
Section: Concentrations Of Opes In Sewage Water and Sludge Along Treacontrasting
confidence: 51%
“…Of all the target compounds in this study, the predominance of TBEP, TCPP and TCEP were also observed in STP wastewater in most developed countries including Spain (Rodriguez et al, 2006;Quintana and Reemtsma, 2006;Garcia-Lopez et al, 2010), Germany (Rodil et al, 2005;Meyer and Bester, 2004), Austria (MartinezCarballo et al, 2007) and Sweden (Marklund et al, 2005) (Table 2). In the present study, raw sewage aqueous phase concentrations of TBEP, TCPP and TCEP were lower than those in surface water in Beijing: 10-740 ng/L TBEP, 145-1359 ng/L TCPP, and 88.4-2918 ng/L TCEP (Gao et al, 2015), which may result from the separation of rain and sewage considering that rainwash can directly bring a plenty of OPEs from soil, dust and airborne particles into the river. Meanwhile, the raw sewage aqueous phase concentrations of these three OPEs were lower than those in most developed countries (Table 2), e.g.…”
Section: Concentrations Of Opes In Sewage Water and Sludge Along Treacontrasting
confidence: 51%
“…These columns contain long alkyl chain ligands with an ionizable terminus which, depending on the functional groups and the pH of the mobile phase, allow them to interact with the analytes by anion‐exchange, cation‐exchange or both, in addition to RP interactions. Several applications of this technology can be found in the pharmaceutical field and, to a minor extent, in the food and environmental field …”
Section: Introductionmentioning
confidence: 99%
“…Several applications of this technology can be found in the pharmaceutical field [28][29][30] and, to a minor extent, in the food 31,32 and environmental field. 33,34 The aim of this study was to develop a new analytical method combining SPE and mixed-mode LC coupled to MS/MS for the determination of COC and its related compounds in wastewater. The analytes selected were the parent drug, its metabolites BE and COE, the pyrolytic products AE and AEME, and levamisole (LEV), one of the main pharmaceuticals used in the adulteration of COC hydrochloride.…”
mentioning
confidence: 99%
“…More common extraction techniques for PFRs include mechanical agitation and pressurized liquid extraction (PLE) . These techniques can be followed by a purification step, such as gel permeation chromatography , on‐line turbulent flow chromatography , or SPE . Traditionally, the most used technique for the analysis of PFRs has been the GC coupled to flame photometric detector , MS , or MS/MS .…”
Section: Introductionmentioning
confidence: 99%